Livestock Farm Recovery Following Bushfire in South-Eastern Australia: Impacts on Cattle and Sheep Health and Management - Megan Thomas; John Webb Ware; Brendan Cowled; Carolina Munoz; Elicia Cheah; Peter Mansell; Henry Clutterbuck; Mark Doyle; Alison Hillman; Caitlin Pfeiffer (Animals, 2025)
Severe bushfires in South-Eastern Australia during the summer of 2019/2020 killed tens of thousands of livestock, while many more survived on fire-affected properties. At the time, the literature on bushfire and livestock in Australia primarily described animals with burns. The mid- to long-term health effects, if any, of fire exposure and the effectiveness of recovery activities for surviving animals and farm enterprises were rarely reported. This study aimed to describe the key impacts of bushfire exposure on the health, welfare, and management of surviving cattle and sheep to inform recommendations for future fire-affected farmers and to guide future research. As part of a broad research programme, data on bushfire experiences, consequences for the livestock and the farm enterprise, and lessons learnt were gathered through face-to-face interviews and an online survey, collating information from 58 fire-affected farmers. A variety of health conditions at low frequency were reported in livestock surviving bushfires, including respiratory disease, eye disease, ruminal acidosis, lameness, and plant toxicities. No single disease was observed widely across participating farms, with many conditions likely associated with management changes post-fire rather than direct fire exposure. A variety of management and farm biosecurity challenges were also described by farmers. Key strategies for the prevention and treatment of health conditions in livestock post-bushfire include supporting effective farm management through the challenges of post-fire recovery and early detection for treatment on a case-by-case basis.